Association of serum lysophosphatidylcholine acyltransferase 3 levels with metabolic variables and risk of type 2 diabetes mellitus: A cross-sectional study - Haifeng Zhu; Ziyi Zhong; Jing Jin; Wei Liu; Yuan Cao; Yawen Guo; Gaonian Zhao; Qian Li (PLoS ONE, 2025)
Aims This study aimed to explore the role of serum lysophosphatidylcholine acyltransferase 3 (LPCAT3) in glucose and lipid metabolism and its association with type 2 diabetes mellitus (T2DM). Methods Between July and December 2024, we recruited 256 newly diagnosed T2DM patients and 252 gender- and age-matched individuals with normal glucose tolerance (NGT). Serum LPCAT3 levels were measured using ELISA. Group comparisons were conducted via t-tests or Mann-Whitney U tests. Spearman correlation analysis assessed the relationship between LPCAT3 and metabolic variables. Linear regression identified independent predictors of LPCAT3 levels. Partial Least Squares (PLS) analysis evaluated the correlations between serum LPCAT3 and obesity-related anthropometric indicators, blood glucose and lipid indicators. Logistic regression evaluated the association between LPCAT3 levels and T2DM risk, and ROC analysis determined its predictive value. Results Median LPCAT3 level was lower in T2DM patients (21.51 ng/ml, IQR: 8.47–35.63) compared to the NGT group (24.43 ng/ml, IQR: 14.41–49.37). In NGT individuals, LPCAT3 negatively correlated with high-density lipoprotein cholesterol (HDL), fasting blood glucose (FBG), and glycated hemoglobin (HbA1c). In T2DM patients, LPCAT3 negatively correlated with body mass index (BMI) and waist circumference (WC). Linear regression identified BMI, HDL, and FBG as negative predictors of LPCAT3. PLS analysis revealed negative correlations between LPCAT3 and BMI, WC, HDL and FBG, but with large standard errors. When stratified by LPCAT3 tertiles, the lowest tertile initially showed a higher T2DM incidence than the highest tertile. However, after adjusting for obesity-related indicators, no significant difference was found between them. ROC analysis yielded an AUC of 0.580 for LPCAT3. Conclusion Although serum LPCAT3 levels are lower in T2DM patients, its predictive capacity for T2DM is constrained. Moreover, the association between LPCAT3 and T2DM risk is likely confounded by obesity-related factors. While LPCAT3 tends to negatively correlate with BMI, HDL, and FBG, these correlations are complex and unstable.